Steppe development on the Northern Tibetan Plateau inferred from Paleogene ephedroid pollen. Issue 1 (2nd January 2016) - Han, Fang; Rydin, Catarina; Bolinder, Kristina; Dupont-Nivet, Guillaume; Abels, Hemmo A.; Koutsodendris, Andreas; Zhang, Kexin; Hoorn, Carina
Abstract: Steppe vegetation represents a key marker of past Asian aridification and is associated with monsoonal intensification. Little is, however, known about the origin of this pre-Oligocene vegetation, its specific composition and how it changed over time and responded to climatic variations. Here, we describe the morphological characters of Ephedraceae pollen in Eocene strata of the Xining Basin and compare the pollen composition with the palynological composition of Late Cretaceous and Paleocene deposits of the Xining Basin and the Quaternary deposits of the Qaidam Basin. We find that the Late Cretaceous steppe was dominated by Gnetaceaepollenites ; in the transition from the Cretaceous to the Paleocene, Gnetaceaepollenites became extinct and Ephedripites subgenus Ephedripites dominated the flora with rare occurrences of Ephedripites subgen. Distachyapites ; the middle to late Eocene presents a strong increase of Ephedripites subgen. Distachyapites ; and the Quaternary/Recent is marked by a significantly lower diversity of Ephedraceae (and Nitrariaceae) compared to the Eocene. In the modern landscape of China, only a fraction of the Paleogene species diversity of Ephedraceae remains and we propose that these alterations in Ephedreaceae composition occurred in response to the climatic changes at least since the Eocene. In particular, the strong Eocene monsoons that enhanced the continental aridification may have played an important role in the evolution of Ephedripites subgen. Distachyapites triggering an evolutionary shift to wind-pollination in this group. Conceivably, the Ephedraceae/Nitrariaceae dominated steppe ended during the Eocene/Oligocene climatic cooling and aridification, which favoured other plant taxa.